Bioaccumulation and potential sources of heavy metal contamination in fish species in River Ganga basin: Possible human health risks evaluation. (2019) - Maurya, Pradip Kumar; Malik, D.S.; Yadav, Krishna Kumar; Kumar, Amit; Kumar, Sandeep; Kamyab, Hesam
Graphical abstract: Highlights: Different pollution degrees have been evaluated to check the pollution level in the River. The concentration of all studied heavy metals in all fish samples were in the order of liver > gill > muscle. The liver and gills of C. catla and C. mrigala were found to have high concentration of Cu and Zn. There is no potential health risk due to the consumption of studied fish species as the THQ value is less than 1. Need special measures must be taken to decrease the health effects of human being near the catchment basin of river. Abstract: This paper assesses the potential human health risks posed by five heavy metals (Zn, Pb, Cu, Cd, and Cr) found in seven most consumable fish species ( Cirrhinus mrigala, Cirrhinus reba, Catla catla, Lebio rohita, Crossocheilus latius, Clupisoma garua, and Mystus tengara ) collected from local markets of Varanasi, Allahabad, Mirzapur, and Kanpur of Uttar Pradesh, India. The Cu concentration was found at Varanasi (4.58 mg/l), Allahabad (2.54 mg/l), and Mirzapur (2.54 mg/l). Pb was recorded 0.54, 0.62, 0.85, and 0.24 mg/l at Kanpur, Allahabad, Mirzapur, and Varanasi, respectively. The Cd concentration was recorded 0.54, 0.68, 0.78, and 0.85 mg/l at Kanpur, Allahabad, Mirzapur, and Varanasi, respectively. The Cr, Cd, and Pb concentrations in the river water were observed over the prescribed safe limits at all sampling sites, while Cu concentration was higher than the standards at all sites except Kanpur. However, Zn was observed under the permissible limits (15 mg/l) at all sampling sites. In case of fish tissues, WHO reported the concentration of Pb, Cd, and Cr higher than the prescribed safe limits. The results determined that the highest heavy metals accumulation was found settled in the liver of all selected fish species. Zn ranked the highest quantity, which was found in fish tissues with the concentration of 32.41 ± 2.55 μg/g in the gill of C. catla and 4.77 ± 0.34 μg/g in the gill C. Reba . The metals followed the magnitude order of Zn > Pb > Cu > Cd > Cr in selected fish tissues.